Description of Pseudomonas jessenii subsp. pseudoputida subsp. nov., amended description of Pseudomonas jessenii and description of Pseudomonas jessenii subsp. jessenii subsp. nov - Kosina, Marcel; Mašlaňová, Ivana; Pascutti-Vávrová, Andrea; Sedo, Ondrej; Lexa, Matej; Svec, Pavel; Sedláček, Ivo (Folia microbiologica, 2013)
Fluorescent Pseudomonas putida CCM 3656 (ATCC 11250) was analysed according to the methods of polyphasic approach which were based on sequence analyses involving the rpoB and rrs genes, manual ribotyping using endonuclease HindIII, DNA base composition determination and DNA-DNA hybridization. The results obtained by these genotyping methods showed that the strain CCM 3656 is distant from P. putida taxon, which was supported with phenotype characterization represented by whole-cell protein profile analysis, matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry profiling and extended biotyping. The DNA-DNA hybridization experiments performed between the strain CCM 3656 and the closest relatives revealed 77 % similarity with Pseudomonas jessenii. However, the outcomes of sequencing, ribotyping and phenotype characterization allow distinguishing the studied strain from P. jessenii. On the basis of the obtained taxonomic data, we suggest reclassifying strain CCM 3656 to a novel subspecies of P. jessenii and propose naming P. jessenii subsp. pseudoputida subsp. nov. with CCM 3656(T) as type strain. Furthermore, we present an amended description of P. jessenii and proposal of P. jessenii subsp. jessenii subsp. nov.
Keywords: proteom; Ribotyping; DNA, Ribosomal; Phylogeny; DNA-Directed RNA Polymerases; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; zastoupení bazí; Cluster Analysis; Base Composition; ribotypizace; sekvenční analýza DNA; spektrometrie hmotnostní - ionizace laserem za účasti matrice; fylogeneze; shluková analýza; ribozomální DNA; Bacterial Typing Techniques; Nucleic Acid Hybridization; Proteome; hybridizace nukleových kyselin; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; techniky typizace bakterií; DNA řízené RNA-polymerasy; Pseudomonas